Local transmission and global dissemination of New Delhi Metallo-Beta-Lactamase (NDM): a whole genome analysis. (December 2016) - Khong, Wei; Xia, Eryu; Marimuthu, Kalisvar; Xu, Wenting; Teo, Yik-Ying; Tan, Eng; Neo, Shiyong; Krishnan, Prabha; Ang, Brenda; Lye, David; Chow, Angela; Ong, Rick; et al.
Abstract Background New Delhi metallo-β-lactamase (bla NDM ), a plasmid-borne carbapenemase gene associated with significant mortality and severely limited treatment options, is of global public health concern as it is found in extremely diverse Gram-negative bacterial strains. This study thus aims to genetically characterize local and global spread ofbla NDM . Methods To investigate local transmission patterns in the context of a single hospital, whole genome sequencing data of the first 11bla NDM -positive bacteria isolated in a local hospital were analyzed to: (1) identify and comparebla NDM -positive plasmids; and (2) study the phylogenetic relationship of the bacteria chromosomes. The global analysis was conducted by analyzing 2749 complete plasmid sequences (including 39bla NDM -positive plasmids) in the NCBI database, where: (1) the plasmids were clustered based on their gene composition similarity; (2) phylogenetic study was conducted for eachbla NDM -positive plasmid cluster to infer the phylogenetic relationship within each cluster; (3) gene transposition events introducingbla NDM into different plasmid backbones were identified; and (4) clustering pattern was correlated with the plasmids' incompatibility group and geographical distribution. Results Analysis of the first 11bla NDM -positive isolates from a single hospital revealed very lowbla NDM -positive plasmid diversity. Local transmission was characterized by clonal spread of a predominant plasmid with 2 sporadic instances of plasmid introduction. In contrast to the low diversity locally, globalbla NDM spread involved marked plasmid diversity with no predominant bacterial clone. Thirty-nine (1.4 %) out of the 2749 complete plasmid sequences werebla NDM -positive, and could be resolved into 7 clusters, which were associated with plasmid incompatibility group and geographical distribution. Thebla NDM gene module was witnessed to mobilize between different plasmid backbones on at least 6 independent occasions. Conclusions Our analysis revealed the complex genetic pathways ofbla NDM spread, with global dissemination characterized mainly by transposition of thebla NDM gene cassette into varied plasmids. Early local transmission following plasmid introduction is characterized by plasmid conjugation and bacterial spread. Our findings emphasize the importance of plasmid molecular epidemiology in understandingbla NDM spread.